2012
DOI: 10.3389/fonc.2012.00089
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation Promotes an M2 Macrophage Phenotype in Tumor Hypoxia

Abstract: Macrophages display different phenotypes with distinct functions and can rapidly respond to environmental changes. Previous studies on TRAMP-C1 tumor model have shown that irradiation has a strong impact on tumor microenvironments. The major changes include the decrease of microvascular density, the increase of avascular hypoxia, and the aggregation of tumor-associated macrophages in avascular hypoxic regions. Similar changes were observed no matter the irradiation was given to tissue bed before tumor implanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(129 citation statements)
references
References 56 publications
3
124
2
Order By: Relevance
“…It has been reported that Treg cells and TAMs both can be enhanced following radiotherapy. [41][42] The dosage of radiotherapy might be a key factor in the reconciliation of this apparent contradiction. 29 LDI has been shown to program macrophage differentiation into an iNOS C /M1 phenotype, leading to normalization of tumor vasculature and facilitation of immune cell entry into tumor sites.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Treg cells and TAMs both can be enhanced following radiotherapy. [41][42] The dosage of radiotherapy might be a key factor in the reconciliation of this apparent contradiction. 29 LDI has been shown to program macrophage differentiation into an iNOS C /M1 phenotype, leading to normalization of tumor vasculature and facilitation of immune cell entry into tumor sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, some chemotherapeutic agents can cause immunogenic cell death and promote anti-tumor immunity (192). Also, despite the antitumor-immune promoting effects of RT, prior irradiation may lead to modification of the tumor microenvironment leading to a more immune-tolerant phenotype (113,193). The net effect of these prior treatments is not clear, but it is likely to have an impact on the immune system and on the effectiveness of cancer immunotherapy.…”
Section: Clinical Approaches: What Have We Learned?mentioning
confidence: 98%
“…There are reports that RT can impair DC function, including cross-priming (109,110). Additionally, RT can contribute to the immunesuppressive tumor microenvironment by recruiting MDSCs and TAMs (76,(111)(112)(113). Tumor-infiltrating Tregs are also enriched after RT (77,114).…”
Section: Anti-immunogenic Effects Of Rtmentioning
confidence: 99%
“…In addition, inhibition of the PD-1/PD-L1 pathway on T cells has been associated with a potent antitumor activity in mouse tumor models and in clinical trials (71,(115)(116)(117).…”
Section: Multimodality Treatments and Future Directionsmentioning
confidence: 99%
“…On the other hand, ionizing radiation can also generate chemotactic signals that recruit several myeloid-cell types with distinct roles in T cell suppression (114)(115)(116).…”
Section: Multimodality Treatments and Future Directionsmentioning
confidence: 99%